2019
DOI: 10.1037/law0000188
|View full text |Cite
|
Sign up to set email alerts
|

A social judgment? Extralegal contrast effects in hypothetical legal decision making.

Abstract: Social judgments in ambiguous situations often rely on heuristics and biases, and legal decision makers are often faced with evidence that does not clearly favor one decision over another. Across two studies, we tested whether one extralegal factor, contrast cases, influenced decision making when judicial factors were held constant. In Study 1, participants (n = 100) evaluated whether an imagined prosecutor had sufficient evidence to send the same three target cases to trial. Before deciding these cases, thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…However, the case study warns that around 1/3 of the judicial agents (34.0, 30.2, and 28.8%, respectively), would attribute, respectively, more responsibility, truthfulness, and prevention capacity to the complainant when the perpetrator is known (statistical model error). Motivational attribution biases refer to a tendency to form and hold beliefs that conform to the needs of the individual, in this case, judgment making and the subsequent decisionmaking, and manifest when the legal evidence is insufficient or weak (week cases; Butterfield and Bitter, 2019), being irrelevant in strong evidence cases (Visher, 1987;Kahneman, 2011). Under this contingency, judicial agents, in judicial judgment and decision making, must be guided by strict compliance with the principle of presumption of innocence (Article 11.1 of the Universal Declaration of Human Rights; United Nations, 1948), which implies that none innocent person may be classified as guilty, so the attributional biases supporting the absolution of the accused of the crime would support the motivation of the procedural action taken or the judicial resolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the case study warns that around 1/3 of the judicial agents (34.0, 30.2, and 28.8%, respectively), would attribute, respectively, more responsibility, truthfulness, and prevention capacity to the complainant when the perpetrator is known (statistical model error). Motivational attribution biases refer to a tendency to form and hold beliefs that conform to the needs of the individual, in this case, judgment making and the subsequent decisionmaking, and manifest when the legal evidence is insufficient or weak (week cases; Butterfield and Bitter, 2019), being irrelevant in strong evidence cases (Visher, 1987;Kahneman, 2011). Under this contingency, judicial agents, in judicial judgment and decision making, must be guided by strict compliance with the principle of presumption of innocence (Article 11.1 of the Universal Declaration of Human Rights; United Nations, 1948), which implies that none innocent person may be classified as guilty, so the attributional biases supporting the absolution of the accused of the crime would support the motivation of the procedural action taken or the judicial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…This research found that in rape cases was attributed more blame to the victim and less blame to the perpetrator compared with robbery cases. Thus, as these sources of bias in judgment making are unconscious for judgment makers and ways of informal reasoning, judicial agents should be trained to control the effects of these sources of bias (Bartels, 2010), promoting debiasing, i.e., substituting informal reasoning (judgment making sustained on biases against the complainant) by formal reasoning sources (evidence, procedural rules, charge of the proof) (Butterfield and Bitter, 2019). In sum, the training and specialization of judicial agents (e.g., courts specialized in sexual assaults, training police forces to obtain the statement from complainants of sexual assault) in sexual violence against women cases is necessary 10.3389/fpsyg.2022.866145 (Barn and Powers, 2021;Gancedo et al, 2021b); so that, from an orientation of Therapeutic Justice, they can mediate the wellbeing of the victims (Cattaneo and Goodman, 2010;Camplá et al, 2020;Novo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation